Lower skeletal extension in Pleistocene Orbicella (Montastraea) corals than in their modern counterparts - Jordán-Garza, Adán Guillermo; Blanchon, Paul; Carricart-Ganivet, Juan P.; Jordán-Dahlgren, Eric (Frontiers in Marine Science, 2023)
Introduction Despite warmer conditions during the Last Interglacial, coral colonies of Orbicella were abundant and reached large sizes on many Caribbean reefs, including the extinct O. nancyi. Methods To explore variation in growth rates, we examined the yearly mean linear extension of growth bands in two fossil Orbicella species and compared them with two modern species of the same genus from shallow waters of the wider Caribbean.We measured the linear extension of corals exposed in a fossil reef and their modern counterparts, from both in situ colonies and coral slab X-rays. Results Few coral colonies showed autocorrelation or a linear trend on their linear-growth time series. A Bayesian ANOVA showed lower linear-extension rates of fossils compared to modern colonies and similar or lower than other fossil corals from the Pleistocene. Growth rates and growth form contribute significantly to the amount of tissue and size of coral colonies and can be a decisive trait for inter and intra specific competition. Discussion It is unlikely that temperature or interspecific competition explain modern coral extension rates and the low rates of the fossils data, which seem to be controlled instead by past habitat conditions.